(untitled) (Economic and Political Thought, 2024)
The article addresses the issue of energy poverty in Central and Eastern European countries in the context of sustainable development and the ongoing energy transition. It highlights the dynamic transformation of the power systems in these countries, which are striving to replace high-emission fossil fuels with low-emission energy sources, including renewables (RES). The article provides a detailed analysis of the relationship between the share of RES in the energy mix and the level and volatility of electricity prices, as well as its impact on the phenomenon of energy poverty.